A two‐level mixed‐integer programming model for bridge replacement prioritization. (12th August 2019) - Zhang, Ning; Alipour, Alice
Abstract: A bridge network is an essential part of the transportation system. Therefore, the restoration and replacement activities of aging bridges result in severe traffic delays and disruptions that heavily impact the daily traffic. Accelerated bridge construction (ABC) techniques are rapidly gaining acceptance as an alternative to conventional construction due to reduced construction duration and minimum closure impact at the network level. The limitations and completion rates vary depending on types of ABC. There is a trade‐off between a faster ABC technique with higher investment and a faster construction of a critical bridge in the network resulting large savings to users. To provide a balanced portfolio of ABC techniques on bridge sites and the prioritization of bridges for replacement, this paper develops a mixed‐integer programming (MIP) model with two levels. In this model, a network‐level scheme is used to select bridges for rapid replacement based on their criticality to the network, and a project‐level scheme is used to optimize the choice of ABC techniques for each selected bridge. To account for the effects of different construction strategies for bridge replacement, the costs associated with each replacement activity are calculated, including direct costs from the actual replacement of bridges and indirect costs experienced by network users due to bridge closures during maintenance. Using the MIP model and based on investment, outcomes are estimated for the enhanced serviceability, efficient ABC techniques, an optimal bridge replacement strategy, and minimized total cost during the entire process. These outcomes could provide decision makers and stakeholders with a complete understanding of the prioritization process at both the network and project levels.